Overview of E-Cigarette (Vape) Usage Behavior in 2021 UMJ FKM Students - Ega Oktavia; Alika Fitri Azizah; Baby Shafira Zaintira; Carlina Surya (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
E-cigarettes were first created in a modern way by a pharmacist from China in 2003 and patented in 2004 and then began to spread throughout the world. The results of a survey conducted by the International Tobacco Control Survey in America, Canada, Australia, and England, currently 29% of former smokers use electronic cigarettes, 7.6% have tried using electronic cigarettes and 46.6% are aware of the existence of electronic cigarettes. Some conditions that can arise from long-term use of nicotine are increased blood pressure and heart rate, as well as an increased risk of developing insulin resistance, type 2 diabetes, and heart disease. This research uses a qualitative approach with a descriptive method. Based on in-depth interviews with the informants, it was found that the informants had various reasons for using vapor, both for health reasons and for environmental reasons. All resource persons also argue that the dominant factor that makes a person use vapor is environmental factors. Meanwhile, when viewed from the behavior of all informants, they do not use vapor continuously but at certain times, even one of the informants still uses conventional cigarettes to be accompanied by vapor.